Assessment of thyroid hormones in full-term neonates with late-onset sepsis - Dhananjay Singh; Amit Agrawal; Jyotsna Shrivastava (Indian Journal of Child Health, 2021)
Background: Neonatal sepsis is a clinical syndrome characterized by signs and symptoms of infection with or without bacteremia in neonatal age. The previous studies found that there might be an association between thyroid hormone profile and outcomes in patients with late-onset of sepsis (LOS). Objective: The objective of the study was to assess the thyroid hormone levels in full-term neonates with late-onset sepsis. Materials and Methods: This analytical prospective cohort study was conducted in the neonatal intensive care unit of a tertiary care teaching institution in Central India. Full-term neonates, with culture-proven LOS, were taken as the study population. Estimation of thyroid hormones (thyroid-stimulating hormone [TSH], T3, T4, fT3, and fT4) among full-term neonates with LOS was assessed and correlated before and after antibiotic therapy. Results: A total of 195 full-term neonates were included in the study. Mean values of TSH, T3, T4, fT3, and fT4 before antibiotic therapy were 5.29±2.11 ?g/ml, 94.4±44.4 ng/dl, 7.25±2.72 ?g/dl, 1.84±0.9 pg/ml, and 1.43±0.458 ?g/dl, respectively, and after antibiotic therapy, the values reach to 9.19±1.63 ?g/ml, 185.3±44.53 ng/dl, 13.29±10.24 ?g/dl, 3.60±0.89 pg/ml, and 2.54±052 ?g/dl, respectively. A significant (p<0.0001) improvement in TSH, T3, T4, fT3, and fT4 after antibiotic therapy was found. S. aureus (15.39%) and Streptococcus (15.39%) were found to be the most common organisms for LOS. Conclusion: Our study showed a significant improvement in TSH, T3, T4, fT3, and fT4 after antibiotic therapy among full-term neonates with LOS. Due to this correlation, thyroid profile can assist in treating newborns with LOS.